Strength of evidence for perioperative use of statins to reduce cardiovascular risk: systematic review of controlled studies - Kapoor, Anmol S (BMJ Publishing Group Ltd., 2006)
Objective To determine the strength of evidence underlying recommendations for use of statins during the perioperative period to reduce the risk of cardiovascular events. Design Systematic review of studies with concurrent control groups. Data sources Four electronic databases, the references of identified studies, international experts on perioperative medicine, and the authors of the primary studies. Review methods Two reviewers independently extracted data from studies that reported acute coronary syndromes or mortality in patients receiving or not receiving statins during the perioperative period. Main outcome measure Random effects summary odds ratios for death or acute coronary syndrome during the perioperative period. Results 18 studies—two randomised trials (n=177), 15 cohort studies (n=799 632), and one case-control study (n=480)—assessed whether statins provide perioperative cardiovascular protection; 12 studies enrolled patients undergoing non-cardiac vascular surgery, four enrolled patients undergoing coronary bypass surgery, and two enrolled patients undergoing various surgical procedures. In the randomised trials the summary odds ratio for death or acute coronary syndrome during the perioperative period with statin use was 0.26 (95% confidence interval 0.07 to 0.99) and the summary odds ratio in the cohort studies was 0.70 (0.57 to 0.87). Although the pooled cohort data provided a statistically significant result, statins were not randomly allocated, results in retrospective studies were larger (odds ratio 0.65, 0.50 to 0.84) than those in the prospective cohorts (0.91, 0.65 to 1.27), and dose, duration, and safety of statin use was not reported. Conclusion The evidence base for routine administration of statins to reduce perioperative cardiovascular risk is inadequate.